LINGUACULTURAL ANALYSES OF ENGLISH SLANG - Hakimova Zamira Xurram qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This research examines the intersection of language and culture in modern English slang based on linguacultural approaches. The research presented in this article analyzes the sociolinguistic and pragmatic functions of slang terms that became popular in the 2010s and 2020s, especially through online platforms and small subcultural groups, and explores how slang encodes identity, community, and other meanings. By selecting and studying six modern slang words from contemporary English, it proves that informal language units are interpreted not only as linguistic units but also as cultural symbols